National Service Training Program (NSTP) : Literacy training service 1 - de Chavez, Robert (Mandaluyong City, Philippines : Books Atbp. Publishing Corp, 2019)
This is brought about by the rapid changes taking place in technology.
Chapter 1. Implementing Rules and Regulations of the National Service Training Program -- 2. The Philippine Constitution -- 3. Self-Awareness and Filipino Values -- 4. Leadership Challenges for the Youth of Today -- 5. Personality Development -- 6. Literacy and Numeracy -- 7. The Teachers and the Learner -- References.
Includes bibliographical references.
Keywords: NATIONAL SERVICE -- STUDY AND TEACHING